O impacto do tempo de formação no entendimento do tratamento da escoliose idiopática em adolescentes segundo as diretrizes internacionais da SOSORT: a survey online study - LINHARES, Natália Albim (2022)
OBJECTIVE: Thus, the aim of the current study was to understand the influence of length of professional experience on the knowledge of Brazilian physical therapists regarding international guidelines for the treatment of AIS. METHODS: The study was conducted using an online questionnaire consisting of 23 questions; divided into eight questions on sociodemographic data and 15 questions based on information provided by the guidelines in the SOSORT 2016. FINDINGS: 506 physiotherapists interviewed comprised the study sample and through this it was possible to verify that there seems to be a failure in primary learning, which must be corrected, so that the EIA identification process is more efficient. This indicates that our Brazilian physical therapists are ill equipped to provide a satisfactory level of care to patients with scoliosis in daily clinical practice. CONCLUSIONS: that the length of experience made a difference when considering knowledge of the treatment of idiopathic scoliosis. The present study showed that time since graduation of six years or more was satisfactory.